Cases, materials and text on contract law - Beale, H G; Fauvarque-Cosson, Benedicte; Rutgers, Jacobien; Vogenauer, Stefan (Oxford Hart, 2019)
"This is the third edition of the widely acclaimed and successful casebook on contract in the Ius Commune series, developed to be used throughout Europe and beyond by anyone who teaches, learns or practises law with a comparative or European perspective. The book contains leading cases, legislation and other materials from English, French and German law as the main representatives of the legal traditions within Europe, as well as EU legislation and case law and extracts from the Principles of European Contract Law. Comparisons are also made to other international restatements such as the Vienna Sales Convention, the UNIDROIT Principles of International Commercial Contracts, the Draft Common Frame of Reference and so on. Materials are chosen and ordered so as to foster comparative study, complemented with annotations and comparative overviews prepared by a multinational team"--
Keywords: Contracts -- Europe; LAW / Comparative; Casebooks (Law)